Efficient solar-thermal energy conversion with surfactant-free Cu-oxide nanofluids. (April 2023) - Moghaieb, Hussein Sayed; Padmanaban, Dilli Babu; Kumar, Praveen; Haq, Atta Ul; Maddi, Chiranjeevi; McGlynn, Ruairi; Arredondo, Miryam; Singh, Harjit; Maguire, Paul; Mariotti, Davide
Abstract: High-specification nanofluids can potentially enable cost-effective and highly efficient solar-to-thermal energy conversion. However, their implementation is adversely affected by poor absorption spectral range and stability challenges of the nanoparticles. Here we demonstrate the synthesis, full characterization and application of Cu-oxide nanoparticles with high optical absorption and long-term stability over many months. The synthesis method, based on a hybrid plasma-liquid non-equilibrium electrochemical process, ensures a very limited environmental impact as it relies on a solid metal precursor while avoiding the use of additional chemicals such as surfactants and other reducing agents. We further investigate the fundamental links between the nanofluid performance and the material and optical properties and produce a theoretical model to determine the energy conversion efficiency. The results show that nanofluids produced with our Cu-oxide nanoparticles can achieve exceptional solar thermal conversion efficiencies close to ∼90% and can provide a viable solution for an efficient solar thermal conversion technology. Graphical Abstract: ga1 Highlights: Full synthesis and characterization of surfactant-free Cu-oxide nanoparticles. In-depth experimental and CFD work on thermal and optical behaviours of nanofluids. Superior solar-thermal conversion efficiency close to 90% at as low as 0.01 vol%. High physical, chemical, and thermal stability under realistic conditions. Our Cu-oxide nanoparticles can deliver best performing DASC nanofluid.